The Potential Impact of Adjunct Digital Tools and Technology to Help Distressed and Suicidal Men: An Integrative Review - Balcombe, Luke; De Leo, Diego (Frontiers in Psychology, 2022)
Suicidal men feel the need to be self-reliant and that they cannot find another way out of relationship or socioeconomic issues. Suicide prevention is of importance worldwide. The much higher rate of suicide in men engenders action. The prelude is a very isolating and severely distressing experience. Men may not realize a change in their thinking and behaviors, which makes it more difficult to get help, thereby interrupting a ‘downward spiral’. Stoicism often prevents men from admitting to their personal struggle. The lack of 'quality' connections and ‘non-tailored’ therapies has led to a high number of men ‘walking out’ on traditional clinical approaches. But there are complicated relationships in motivations and formative behaviors of suicide. Middle-aged and older men alternated as the most at-risk of suicide. There is no one solution that applies to all men, but digital tools may be of assistance (e.g., video conferences, social networks, telephone calls, emails). Digital interventions require higher levels of effectiveness for distress and suicidality but self-guided approaches may be the most suitable for men especially where linked with an integrated online suicide prevention platform (e.g., quick response with online chats, phone calls and emails). Furthermore, technology-enabled models of care offer promise to advance appropriate linking to mental health services through better and faster understanding of the specific needs of individuals (e.g., socio-cultural) and the type and level of suicidality experienced. Long-term evidence for suicidality and its evaluation may benefit from progressing human computer-interaction and providing impetus for an eminent integrated digital platform.